Refleksi Evaluatif Pendidikan Karakter Mahasiswa di Sekolah Tinggi Agama Buddha di Indonesia - Sadtyadi, Hesti (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
This study aims to obtain an overview of the character of the students of Buddhist Religious Colleges in Indonesia, which can provide an actual picture of the results of the learning process, particularly about the character of students in the Buddhist Colleges in Indonesia. This research is a survey research, based on Mix Method, both qualitative and quantitative, so it can be called as Mix Method research. All sections used in this research are part of the evaluation of the reflection on character education that has been carried out. The results showed that the instrument for assessing the character of Buddhist College students had good validity and reliability, which could be arranged based on the dimensions: Honesty, Caring, Independence, Discipline, Responsibility, Hard work, Simplicity, Courage, Justice. Based on the analysis of evaluative reflection, both qualitative and quantitative data indicate that Buddhist College students have good character of integrity, despite the fact that they still have to reconsider students' hard work, as well as attention to the caring aspect.